Boundary-enhancement in propagation-based x-ray phase-contrast tomosynthesis improves depth position characterization. (2nd April 2015) - Guan, Huifeng; Xu, Qiaofeng; Garson, Alfred B; Anastasio, Mark A
Abstract: Propagation-based x-ray phase-contrast (PB XPC) tomosynthesis combines the concepts of tomosynthesis and XPC imaging to realize the advantages of both for biological imaging applications. Tomosynthesis permits reductions in acquisition times compared with full-view tomography, while XPC imaging provides the opportunity to resolve weakly absorbing structures. In this note, an investigation of the depth resolving properties of PB XPC tomosynthesis is conducted. The results demonstrate that in-plane structures display strong boundary-enhancement while out-of-plane structures do not. This effect can facilitate the identification of in-plane structures in PB XPC tomosynthesis that could normally not be distinguished from out-of-plane structures in absorption-based tomosynthesis.